2018
DOI: 10.1111/ncn3.12223
|View full text |Cite
|
Sign up to set email alerts
|

Treatment consensus for management of polymyositis and dermatomyositis among rheumatologists, neurologists and dermatologists

Abstract: Although rheumatologists, neurologists, and dermatologists see patients with polymyositis (PM) and dermatomyositis (DM), their management appears to vary depending on the physician's specialty. The aim of this study was to establish the treatment consensus among specialists of the three fields to standardize the patient care. We formed a research team supported by a grant from the Ministry of Health, Labor, and Welfare, Japan. Clinical questions (CQ) on the management of PM and DM were raised. A published work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 198 publications
(408 reference statements)
0
7
0
Order By: Relevance
“…Overall, the patients took a median of 6 months to switch between treatments, suggesting that patients initiating treatment with steroids continued for a long time before switching, thus experiencing a burden (steroid myopathy affecting muscle recovery) due to steroid-related side effects. Thus, a high glucocorticoids (GC) dose is recommended to avoid myositis while keeping the treatment period as short as possible [ 8 ]. This burden could be the reason for the difference in the choice of treatment between two LoTs, which is also reported in previous studies that comorbidities do influence treatment choice and might also further complicate treatment operation for patients who switched multiple therapies in the past [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, the patients took a median of 6 months to switch between treatments, suggesting that patients initiating treatment with steroids continued for a long time before switching, thus experiencing a burden (steroid myopathy affecting muscle recovery) due to steroid-related side effects. Thus, a high glucocorticoids (GC) dose is recommended to avoid myositis while keeping the treatment period as short as possible [ 8 ]. This burden could be the reason for the difference in the choice of treatment between two LoTs, which is also reported in previous studies that comorbidities do influence treatment choice and might also further complicate treatment operation for patients who switched multiple therapies in the past [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This burden could be the reason for the difference in the choice of treatment between two LoTs, which is also reported in previous studies that comorbidities do influence treatment choice and might also further complicate treatment operation for patients who switched multiple therapies in the past [ 26 ]. Other studies have also reported systemic corticosteroids as the most recommended initial therapeutic agent in PM/DM patients [ 8 ] while immunosuppressors being useful in inducing/maintaining remission/experiencing intolerable side effects with steroids in DM patients [ 33 , 34 ]. Few studies have reported cyclosporin A (CsA) administration resulting in 75% reduction in the GC dose [ 35 ] and muscle recovery in JDM patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment for primary DM consists of glucocorticoids and/or glucocorticoid-sparing regimens guided by a rheumatologist. Glucocorticoids are initiated at high doses until improvement of symptoms, which can take weeks, followed by a slow taper over 1 year ( Kohsaka et al, 2019 ). When DM fails to respond to glucocorticoids or individuals have contraindications to steroids, other options include methotrexate, cyclophosphamide, cyclosporin A, rituximab, and IVIG.…”
Section: Discussionmentioning
confidence: 99%